Ancient Egypt - Nardo, Don, 1947- (Civilizations of the world (Focus Readers (Firm)), 2020)
Explores ancient Egyptian civilization from 5000 B.C.E. on, focusing on their rulers, religion, daily life, rise and fall, and ways of writing. Includes color photographs and illustrations, critical thinking questions, a glossary, and an index.